Innovations towards sustainable agri-food system transformation. Key strategic achievements - International Potato Center (International Potato Center, 2020)
With nearly 50 years of research-for-development work in potato and sweetpotato based agri-food systems, the International Potato Center (CIP) has contributed to greater food and nutrition security, and economic growth for millions of small-scale farmers and resource-poor consumers worldwide. This document examines how a selection of CIP’s research-for-development innovations are helping the sustainable transformation agri-food systems with root and tubers crop and science.